Cutaneous sarcoidosis masquerading as chronic cutaneous lupus erythematosus - case report. Issue 1 (December 2016) - Vatanchi, Marjon; Sobhani, Kaivon; Fisher, Valerie; Meffert, Jeffrey
Abstract Background Sarcoidosis is a multisystemic granulomatous disease of unknown origin. Chronic cutaneous lupus erythematosus (CCLE) is an autoimmune disease that is associated with autoantibody production and T-cell dysfunction. Cutaneous manifestations of sarcoidosis may mimic CCLE and vice versa making it difficult to reach a diagnosis clinically. Case presentation We present a case of a 57-year-old woman with long-standing sarcoidosis who presented to clinic with diffuse painful plaques that were very distinct and suggestive of CCLE. She had a family history of both sarcoidosis and CCLE. The patient was immediately started on topical corticosteroids and oral hydroxychloroquine. Skin biopsy and the absence of direct immunofluorescence confirmed a skin manifestation of her previously diagnosed sarcoidosis, despite the clinical morphology favoring classic CCLE. Conclusion Sarcoidosis may have diverse manifestations and may mimic other disease processes. A detailed history along with a low threshold for biopsy is important for determining a diagnosis.